Study of the influence of protein food on the development and productivity of queen bees - N. Perig (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки, 2022)
The development of crop and animal husbandry is not possible without bees. Moreover, in beekeeping, emphasis is placed on reproducing honey bees to increase the aerial collection work. To solve the tasks, specialists work to improve the honey base, breed and keep bees, etc. Moreover, the main factor that affects the productivity level is the quality of the uterus. There is a need for additional study of factors that positively affect oogenesis in honey bee queens. The work aimed to study the influence of high-protein nutrition on the growth and development of Carpathian queens. The article presents data on the influence of feed quality on the exterior and interior indicators of reared bees and infertile queens. Three groups of families-teachers have been formed. In the families of the control group, all perg frames were removed. However, flying bees had free access to pollinators within the productive flight. The mass of carbohydrate feeds ranged from 8 to 9 kg. The bees of the first experimental group had the opportunity to consume perga from more than 15 types of plants. The most significant mass fraction of feed was perga formed from apple pollen. As protein fodder, families were given two perg honeycombs with a total weight of 1.1–1.3 kg. The protein content in the feed of the first group averaged 19.5 ± 1.2 %, and total lipids – 6.7 ± 0.5 %. The same mass of perga was placed in the nests of the II research group – female tutors. However, 80–90 % of the perg frames were formed from bee pollen of winter rapeseed. The average protein content in the samples taken from the perga combs of the second research group was 26.4 ± 1.4 %, and total lipids – 7.5 ± 0.3 %. As a result of the consumption of these feeds in the first experimental group, the maximum load of the honey bee was 57.3 mg, which is 10.9 % more compared to the control (Р< 0.05). Positive dynamics regarding the mass of nectar in the hive of flying bees were found in the bees of the II research group. The average weight in this group was 15.3 % higher than the control's and was 57.3 ± 1.16 (Р < 0.01). The acini size of the pharyngeal glands was significant (Р < 0.001) in bees that were additionally fed with rapeseed bee pollen. It should be noted that the consumption of feed containing 26.5% protein caused an increase in the size of secretory cells by 21.8 %.